A Costly Cure: Understanding and Addressing Financial Toxicity in Cardiovascular Disease Health Care Within the Domain of Social Determinants of Health - Vijay Aaroha Kandula; Grace Li Smith; Ravi Rajaram; Nicolas L. Palaskas; Anita Deswal; Khurram Nasir; Hyeon-Ju Ryoo Ali (Methodist DeBakey Cardiovascular Journal)
Cardiovascular disease (CVD) represents a significant financial burden on patients and families, compounded by both direct and indirect healthcare costs. The increasing prevalence of CVD, coupled with the rising costs of treatment, exacerbates financial toxicity—defined as the economic strain and associated physical, emotional, and behavioral consequences on patients. This review explores the scope of financial toxicity in CVD care, detailing its prevalence, associated risk factors, and the complex interplay with social determinants of health such as income, insurance status, and comorbidities. Drawing from models in oncology, we highlight key interventions aimed at mitigating financial toxicity, including patient counseling, financial navigation, and enhanced patient-physician cost discussions. By adopting these approaches, healthcare providers can better support patients with CVD in managing both their health and financial well-being, potentially improving clinical outcomes. Future research is needed to develop standardized assessment tools for financial toxicity in CVD and implement system-wide mitigation strategies.